International Repatriations of Indigenous Human Remains and Its Complexities: the Australian Experience - Turnbull, Paul (Museum and Society, 2020)
In this article, I discuss how returns of Ancestral Remains of Indigenous Australian communities from overseas museums and other scientific institutions since the early 1990s have occurred in the context of changing Australian government repatriation policies and practices. The article then highlights how the past three decades have seen numerous instances of the return of Ancestral Remains to their community proving difficult and stressful because of the loss of ancestral lands, life-ways and the experience of colonial subjugation. As I explain, returning the dead has challenged the living by requiring them to address questions of authority, power and historical legacies of colonialism, notably in the case of those communities seeking the restoration of ownership of their ancestral country within the framework of Australia’s current national and state land laws.